This preview shows page 1. Sign up to view the full content.
Unformatted text preview: f test1 = test1 + f(i); t end e comptrapn4 = (b-a)*(f(a) + 2*test1 + f(b))/(2*n) c mid = (a+b)/2; m simp = (b-a)*(f(a) + 4*f(mid) + f(b))/6 s compsimp = (b-a)*(f(a) + 4*(f(a+h) + f(a+3*h)) + 2*f(a+2*h) + f(b))/(3*n) c function new = f(x) f new = 1 - exp(-2*x); n...
View Full Document
This note was uploaded on 09/21/2011 for the course EGM 3344 taught by Professor Raphaelhaftka during the Spring '09 term at University of Florida.
- Spring '09